Synergistic effects of Bacillus subtilis QST 713 and L-arginine supplementation during late gestation on reproductive performance in Landrace × Yorkshire sows: A randomized controlled trial - Thepsavanh Khoudphaithoune; Do Thi Kim Lanh; Nguyen Van Thanh; Bui Van Dung; Peerapol Sukon; Nguyen Hoai Nam (Veterinary World)
Background and Aim: Low birth weight and within-litter variations are major challenges in swine production, often exacerbated by highly prolific sow lines. Nutritional interventions such as amino acid and probiotic supplementation have shown promise, but their combined effects remain unexplored. This study aimed to evaluate the individual and interactive effects of Bacillus subtilis QST 713 and L-arginine supplementation during late gestation on reproductive performance in sows.